Clinical Implications of Phenotypes of Hemodialysis Patients With Central Venous Occlusion or Central Venous Stenosis Defined by Cluster Analysis - Wen, Chunyong; Chen, Bin; Lin, Run; Dai, Haitao; Tang, Keyu; Zhang, Guiyuan; Huang, Jiawen; Liao, Changli; Zeng, Linyuan; Xiang, Xianhong; Yang, Jianyong; Huang, Yonghui (Frontiers in Cardiovascular Medicine, 2022)
Objective This study aims to investigate the association between clinical factors of patients with central (superior vena cava, brachiocephalic, or subclavian) venous occlusion or central venous stenosis (CVO/CVS) and the difficulty of interventional recanalization as well as the duration of postoperative patency. Methods A total of 103 hemodialysis patients with CVO/CVS treated with endovascular treatment were enrolled. The two-step cluster analysis was selected to differentiate the cases into distinct phenotypes automatically. Differences in characteristics, the difficulty of interventional recanalization, and the duration of postoperative primary patency time between the two clusters were statistically compared. Results The 103 cases were divided into distinct two clusters by the two-step cluster analysis with 48 (46.6%) in cluster 1 and 55 (53.4%) in cluster 2. Compared to cluster 2, patients in cluster 1 have a higher proportion of blunt stump, side branches, occlusion lesions >2 cm, calcification, or organization. Moreover, the above four factors were, in turn, the most critical four predictors distinguishing 103 patients into two clusters. The remaining six factors were, in turn, occlusion located in the superior vena cava (SVC), duration of central venous catheterization (CVC), lesion location, vessel diameter, number of CVC, and previously failed lesion. Of the four most important factors, with the exception of occlusion lesions exceeding 2 cm, there were significant differences in the length of procedure time between the groups grouped by the remaining three factors. And there was a significant difference in the primary patency rate between the group with blunt stump and the group without blunt stump and also between the group with occlusion lesions ≥ 2 cm and the group with occlusion lesions <2 cm. The operation time of cluster 1 was longer than that of cluster 2. In terms of postoperative patency time, the primary patency time was significantly longer in the patients of cluster 2 compared with cluster 1 (P = 0.025). Conclusion Patients were divided into distinct two clusters. CVO/CVS of patients in cluster 1 was more challenging to be recanalized than that in cluster 2, and the primary patency time was significantly longer in the patients of cluster 2 compared with cluster 1. Blunt stump, side branches, occlusion lesions exceeding 2 cm, and calcification or organization are the four most critical predictors distinguishing 103 patients into two clusters.